BASIC TENDENTIOUS ON DIFFUSIONS AND NUMERAL LITTLE MAMMALS, DETERMINATION DYNAMIC NATURAL- CLIMATICALLY FACTORS (FOR EXAMPLE SORT CHIONOMYS OF CAUCASUS) - A. M. Sigageva; R. I. Dgyev (Юг России: экология, развитие, 2014)
Completely results (morphology, cariology, molecular – genetics) of subspecies Chionomys on Caucasian deserves differences three species: Chionomys gud, Chionomys nivalis, Chionomys roberti. Areal subspecies in Caucasian is very difficult and specif-ic, that connect with landscape and history becoming. Beside, ecology, cariology and molecular-genetics facts tell about our species have monophyletic relationships.